Overview of the Caucasian Perla Geoffroy, 1762 (Plecoptera: Perlidae) based on morphological and molecular data with description of two new species - Teslenko, Valentina A.; Palatov, Dmitry M.; Semenchenko, Alexander A. (Zootaxa, 2024)
Six species of Caucasian Perla are reviewed, and diagnostic morphological characteristics of all stages of development (where possible) are described, supplemented, and illustrated in detail with comparative light microscope and scanning electron microscopy images. The DNA barcoding of five species is presented. Two new morphologically and genetically distinct species, Perla schapsugica sp. nov. and Perla palatovi sp. nov., are described for both sexes and all life stages in the North Caucasus, Russia, Krasnodar Kray. Reinstatement of Perla persica Zwick, 1975, as a valid species distinct from P. caucasica Guérin-Méneville, 1843, is proposed. A new record of P. persica is reported for the Greater Caucasus, Russia, North-Ossetia-Alania for the first time. Morphologically, these two latter species can be separated in male adults by the shape of the hemitergal hook on terga X, an additional ventral brush on the penis of P. caucasica, wing length, and color.